STANCE ADVERBIALS IN TRIPADVISOR REVIEWS: A CORPUS-BASED ANALYSIS OF DIGITAL TOURISM DISCOURSE - Gema Febriansyah; Dan Fareth B. Fajardo (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2026)
Online hotel reviews have become a routine part of how travelers decide where to stay, and they give linguists a large pool of naturally produced evaluative language to study. This paper looks at one grammatical resource that reviewers rely on to express judgment: the stance adverbial. We built a small specialized corpus, the Indonesian Tourism Review Corpus (ITRC), made up of 120 English-language TripAdvisor reviews (32,147 words) of hotels in Bali, Jakarta, and Yogyakarta, and analyzed it using Biber and Finegan’s (1989) categories of epistemic, attitudinal, and style stance. A second coder checked 20% of the data, with a Cohen’s kappa of 0.85. Epistemic adverbials were the most common (68.3%), ahead of attitudinal (24.1%) and style (7.6%) forms, and the overall rate of 272.5 per 10,000 words sits above academic prose but close to journalism. Reviewers leaned heavily on boosters such as “definitely” and “absolutely” to push positive evaluations, while softening criticism with hedges. Rather than treat these as simple style choices, we read them as identity work: writing in English as a lingua franca, reviewers use confident stance marking to come across as experienced, trustworthy travelers on a platform where credibility is always in question. Because the corpus is small and limited to a single platform, we read these patterns as characteristic of this review genre rather than as representative of digital tourism discourse as a whole. We close with practical suggestions for teaching evaluative language in ESP and hospitality courses.